PARTICIPATION OF MALE ASSEPTORS IN THE PROGRAM FAMILY PLANNING, KASUI DISTRICT, WAY KANAN REGENCY, LAMPUNG PROVINCE - Zesty Miranda; Asmaria; M. Fikri Akbar; Maryam (International Journal of Social Science, 2022)
The National Family Planning Program is one of the programs to improve the quality of the population, the quality of human resources, health and social welfare which has so far been implemented through birth control, maturing the age of marriage, increasing family resilience and family welfare. The policy to increase the participation of men in family planning and reproductive health was only launched in the new era of family planning in 2000. The policy of increasing the participation of men in family planning is still relatively new so that the implementation in the field is still uneven. Some have implemented the policy, some have just been socialized and some have not been touched at all. One of the many targets that will be achieved by the family planning program in the long term in order to achieve quality families in 2021. The purpose of this study was to determine the participation of male acceptors in the family planning program. This research is a qualitative research which contains descriptive research and tends to use analysis. The results of this research will be published in national or international journals.